Long term failure of endoscopic gastroplication (EndoCinch). Issue 6 (11th May 2005) - Schiefke, I; Zabel-Langhennig, A; Neumann, S; Feisthammel, J; Moessner, J; Caca, K
Abstract : Introduction: Endoluminal gastroplication (EndoCinch; Bard) has been introduced as an endoscopic treatment option in gastro-oesophageal reflux disease (GORD) patients with promising short term results. However, little is known about the long term efficacy of endoscopic suturing. The aim of this study was to evaluate prospectively the long term outcome after EndoCinch. Patients and methods: A total of 70 patients treated with EndoCinch at a single referral centre were studied prospectively. All patients were interviewed using a standardised questionnaire regarding their symptoms and medication prior to and 18 months after EndoCinch. In addition, follow up included endoscopy, 24 hour pH monitoring, and oesophageal manometry. Results: The procedure was well tolerated without major short or long term complications. Eighteen months after EndoCinch, 56/70 patients (80%) were considered treatment failures as their heartburn symptoms did not improve or proton pump inhibitor medication exceeded 50% of the initial dose. Endoscopy showed all sutures in situ in 12/70 (17%) patients while no remaining sutures could be detected in 18/70 (26%). In 54 and 50 patients examined, respectively, no significant changes in 24 hour pH monitoring (median pH <4/24 hours, 9.1% v 8.5%; p = 0.82) or lower oesophageal sphincter (LOS) pressure (7.7 v 10.3 mm Hg; p = 0.051) were observed while median LOS length slightly increased (3.0 to 3.2 cm; p<0.05). Conclusion: Endoscopic gastroplication (EndoCinch) is a safe and minimally invasive endoscopic treatment for GORD with reasonable short term results. In contrast, long term outcome is disappointing, probably due to suture loss in the majority of patients. Therefore, technical improvements to ensure suture durability are mandatory before endoscopic suturing can evolve as a therapeutic option for GORD treatment.